2018
DOI: 10.3390/atmos9090357
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization, and Validation of a Cold Stage-Based Ice Nucleation Array (PKU-INA)

Abstract: A drop-freeze array (PeKing University Ice Nucleation Array, PKU-INA) was developed based on the cold-stage method to investigate heterogeneous ice nucleation properties of atmospheric particles in the immersion freezing mode from −30 to 0 °C. The instrumental details as well as characterization and performance evaluation are described in this paper. A careful temperature calibration protocol was developed in our work. The uncertainties in the reported temperatures were found to be less than 0.4 °C at various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…INP measurements in the immersion mode were conducted using the PeKing University Ice Nucleation Array (PKU-INA). PKU-INA is a cold-stage-based ice nucleation array (Chen et al, 2018a). The sampled filter of each stage was completely submerged in 20 mL double-distilled water (resistivity of 18.2 M cm −1 at 25 • C).…”
Section: Inp Measurementsmentioning
confidence: 99%
“…INP measurements in the immersion mode were conducted using the PeKing University Ice Nucleation Array (PKU-INA). PKU-INA is a cold-stage-based ice nucleation array (Chen et al, 2018a). The sampled filter of each stage was completely submerged in 20 mL double-distilled water (resistivity of 18.2 M cm −1 at 25 • C).…”
Section: Inp Measurementsmentioning
confidence: 99%
“…Mineral dust has high spatial and temporal variability, impacting atmospheric, oceanic, biological, terrestrial and human systems (Garrison et al, 2003;Gat et al, 2017;Jickells et al, 2005;Mahowald et al, 2014;Mazar et al, 2016;Middleton and Goudie, 2001). Each year, gigatons of dust are transported globally over long distances, dominating the atmospheric aerosol mass and aerosol optical depth (AOD) (Chiapello et al, 1999;Tegen and Fung, 1994;Ben-Ami et al, 2010;Prospero, 1999;Koren et al, 2006). Though the exact property of an aerosol that determines its ice nucleation ability remains unclear, it was consistently shown that the mineral composition plays an important role (Kanji et al, 2017) and that for a certain mineral type, larger particles are more effective heterogeneous INPs than small ones (Archuleta et al, 2005;Lüönd et al, 2010;Welti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid frost during cooling, high-purity dry nitrogen was delivered into the cold stage during the measurement. The temperature uncertainty was less than ± 0.4 ℃ at the various cooling rates (Chen et al, 2018a).…”
Section: Inp Measurementsmentioning
confidence: 81%
“…PKU-INA is a cold stage-based ice nucleation array, operated after careful temperature calibration (Chen et al, 2018a). The sampled filter of each stage was completely submerged in 20 mL double-distilled water (resistivity of 18.2 MΩ• cm at 25 ℃).…”
Section: Inp Measurementsmentioning
confidence: 99%